Annexin II Light Chain p11 Interacts With ENaC to Increase Functional Activity at the Membrane - Cheung, Tanya T.; Ismail, Noor A. S.; Moir, Rachel; Arora, Nikhil; McDonald, Fiona J.; Condliffe, Steven B. (Frontiers in Physiology, 2019)
The epithelial Na+ channel (ENaC) provides for Na+ absorption in various types of epithelia including the kidney, lung, and colon where ENaC is localized to the apical membrane to enable Na+ entry into the cell. The degree of Na+ entry via ENaC largely depends on the number of active channels localized to the cell membrane, and is tightly controlled by interactions with ubiquitin ligases, kinases, and G-proteins. While regulation of ENaC endocytosis has been well-studied, relatively little is understood of the proteins that govern ENaC exocytosis. We hypothesized that the annexin II light chain, p11, could participate in the transport of ENaC along the exocytic pathway. Our results demonstrate that all three ENaC channel subunits interacted with p11 in an in vitro binding assay. Furthermore, p11 was able to immunoprecipitate ENaC in epithelial cells. Quantitative mass spectrometry of affinity-purified ENaC-p11 complexes recovered several other trafficking proteins including HSP-90 and annexin A6. We also report that p11 exhibits a robust protein expression in cortical collecting duct epithelial cells. However, the expression of p11 in these cells was not influenced by either short-term or long-term exposure to aldosterone. To determine whether the p11 interaction affected ENaC function, we measured amiloride sensitive Na+ currents in Xenopus oocytes or mammalian epithelia co-expressing ENaC and p11 or a siRNA to p11. Results from these experiments showed that p11 significantly augmented ENaC current, whereas knockdown of p11 decreased current. Further, knockdown of p11 reduced ENaC cell surface population suggesting p11 promotes membrane insertion of ENaC. Overall, our findings reveal a novel protein interaction that controls the number of ENaC channels inserted at the membrane via the exocytic pathway.